If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 + -2 = 5 Reorder the terms: 9 + -2 + 3x = 5 Combine like terms: 9 + -2 = 7 7 + 3x = 5 Solving 7 + 3x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = 5 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = 5 + -7 3x = 5 + -7 Combine like terms: 5 + -7 = -2 3x = -2 Divide each side by '3'. x = -0.6666666667 Simplifying x = -0.6666666667
| (1-14+x)/23=15 | | 4x^2=3x-2 | | 10y+7-4y=-5+6y+22. | | 1/x^2-1 | | (3+4)+z=(4+8)+3 | | (5t-20)/(4-t) | | 1/2=(4n-6)=11 | | 6y-12=3x | | 4x-2=6t+6 | | 23=35-x | | 3y-x-5=20 | | d^6y/(dx)^6-d^3y/(dx)^3=0 | | 3(y+5)+6(y-4)+2= | | -5-6x=3-(x-5) | | -2x-6=2x+6. | | x=(3-2e^3)/(e^3-1) | | -10(x-1)=10-10x. | | -4x^2+19x-30=0 | | 6(x-1)=6x-1. | | 1-14+x/23=15 | | 3/4y-(y-1/3)=1/12(y-4) | | -4x^2-19x-30=0 | | 5.5=13-3x | | -2y+1=y-5. | | 8x-10y-7y+5x+11= | | y=-5/2x=3 | | 3x^2-6x+2= | | -7u-38=4(u+7) | | C=2.50y+13 | | Y=4x^2-15x-4 | | -9(x-1)=7x-39 | | 6-0+2/2= |